DETERMINATION OF DELTAMETHRIN RESIDUES IN MANDARIN ORANGE AND STUDYING ITS PHYSIOLOYICAL EFFECTS ON MALE MICE BLOOD PROFILE - &et al., Jawad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Deltamethrin insecticide was highly toxic to mammals and had long-term residual effects and easily causing environmental pollution. The dependence concentration of deltamethrin (25 ppm) was used to treat unripe mandarin orange fruits through a field experiment. A daily and weekly fruit samples, up to 35 days, were examined for deltamethrin residues. The concentrations of deltamethrin which immigrated via peel into flesh of mandarin orange were 3.4, 3.9, 4.5 and 5.2 ppm after 1, 2, 3 and 4 days respectively. The levels of deltamethrin residues were decreased (due to many degradation reasons) from the maximum amount (after 4 days) to undetectable amount after 35 days. The field experiment showed that the fruits are ready to consume (matured) after 21 days, at this time, the deltamethrin residue was 2.3 ppm in mandarin fruit flesh, while the Maximum Residue Level of deltamethrin recommended is 0.02 mg/kg. Dealing with the peel part of fruits, at zero time, the mandarin orange peel trapped more than 40% of the initial concentration (25 ppm) of deltamethrin. The effect of 0, 2, 4, 6 and 8 ppm deltamethrin, on blood profile of male mice was determined.